ANALISIS ANTRIAN RAWAT JALAN POLIKLINIK LANTAI 1, LANTAI 3 DAN PENDAFTARAN RSUP Dr. KARIADI SEMARANG - Vita Dwi Rachmawati; Sugito Sugito; Hasbi Yasin (Jurnal Gaussian, 2013)
Hospital is an organization social and health that provides complete (comprehensive), the healing of disease (curative) and disease prevention (preventive) to the public. Hospital quality can be know from the professionality hospital personnel, efficiency, and effectiveness of services.The duration of registration procedure  and service for doctor consultation can affect patient satisfaction of Outpatient Hospital Dr. Kariadi Semarang in obtaining health care. Therefore, it’s necessary queuing models that suitable. so as to obtainable an effective service, balance and efficient which can reduce the long queues and long waiting time. From the analysis, obtainable queuing models at the registration that is (M/M/8):(GD/∞/∞) with the counter number 8 server. In the vct-cst polyclinic and child development polyclinic the model is (M/M/1):(GD/∞/∞) with the number of server 1 doctor while for the nervers polclinic, child health, internal disease, gynecologic and obstetrics, cdc, general surgery, hemodialysis and kb, fertility and the test tube babies that is (M/M/c): (GD/∞/∞) with the number of servers depending on each clinic.